Analisis Kiasan Wakaf Terhadap Wakaf Jiwa Di Pondok Modern Darussalam Gontor - Setiawan bin Lahuri; Rima Alaidi (Universitas Darussalam Gontor, 2018)
Waqf is one of the Islamic organizations that are social,religious worth, and as devotion to God Almighty. Historically,endowments is an instrument Maliyah, which as it pertainedto the teachings of Shariah that is sacred and holy, but theunderstanding and implementation of these endowmentsbelonging to the fiqh (humanitarian efforts); Therefore, it can beunderstood that the practice and realization of the endowmentsare closely related to realistas and interests of people in each ofthe Muslim countries (including Indonesia). Waqf continues todevelop significant paradigm along with adjustments to the rulesthat are ijtihadi and application of endowments in certain areaswith the dimensions of the ever-changing history. One pesantrenin Indonesia has implemented a system of endowments, butin addition to implementing a productive waqf system, theyalso adopted a system that is not a lot of mental endowmentswe have encountered in Indonesia and in various countries.Waqf property type is not only eternal, but many do not know,it kind of waqf property there is impermanent nature, the soul.